A Qualitative Study on AI Tool Adoption in Higher Education: A Cross-National Perspective - Princy Anton, Arockia Packia; Thiru, Murugan (INTI International University, 2025)
Artificial Intelligence (AI) is currently integrated into most sectors, including education. AI tools within Higher Education (HE) have been shown to enhance students' academic performance, learning outcomes, and research productivity. The study addresses the adoption and application of AI tools in HE based on comparison of experiences of two nations. It is centered on exploring perceptions and challenges of teachers and students in integrating AI into pedagogical practices. Researcher adopting a qualitative research approach. Data were collected through interviews and focus groups such that there could be a deep understanding of the users' experience. Results show the cross-national difference in issues like awareness, accessibility, etc. for integrating AI. Research states that AI tools imply huge promise, and their successful use depends on digital literacy, policy contexts, and institutional readiness. On the basis of the result, the outcomes that contributed towards the policy makers are the Generative AI in the Academic syllabus at the tertiary level. In the future, a quantitative method will be added to this research to ensure high accuracy in this research